Comparison of the Moisture Absorption Rate of Polyurethane without Additives and with Addition of Straw, Lime Powder and Stirrup Granules - رواد شكوحي (Latakia University Journal -Engineering Sciences Series, 2023)
The research aims to compare the moisture absorption rate of polyurethane before and after the addition of materials. Samples of this substance were made with different percentages of polyisocyanate and polyols, (which are organic compounds derived from oil), which are its two components. Where the following materials ( Straw,calcinepowder,and styrepor granules) were added to it in order to study the moisture absorption rate of polyurethane, where the moisture absorption rate of samples of this insulation material was measured, at different percentages of polyisocyanate and polyol with additions and without additions to another material, in the end, it was concluded that the addition of straw and lime powder increases the moisture absorption rate,and the addition of Stirbor granules reducer the moisture absorption rate at all proportions of this material.